2013
DOI: 10.1371/journal.pone.0067855
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Actin Is Involved in Modulating Erythropoiesis during Development by Fine-Tuning Gata2 Expression Levels

Abstract: The functions of actin family members during development are poorly understood. To investigate the role of beta-actin in mammalian development, a beta-actin knockout mouse model was used. Homozygous beta-actin knockout mice are lethal at embryonic day (E)10.5. At E10.25 beta-actin knockout embryos are growth retarded and display a pale yolk sac and embryo proper that is suggestive of altered erythropoiesis. Here we report that lack of beta-actin resulted in a block of primitive and definitive hematopoietic dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 43 publications
0
20
1
Order By: Relevance
“…In the few studies that used beta-actin ablation in mouse models, apoptosis was never studied. However, we recently demonstrated a role for beta-actin in cell homeostasis and as a transcriptional modulator of Gata2 during mouse embryogenesis [10], [12]. Nuclear functions of actin have been contested for more than 20 years but a role for actin as a transcriptional modulator is now firmly established.…”
Section: Discussionmentioning
confidence: 99%
“…In the few studies that used beta-actin ablation in mouse models, apoptosis was never studied. However, we recently demonstrated a role for beta-actin in cell homeostasis and as a transcriptional modulator of Gata2 during mouse embryogenesis [10], [12]. Nuclear functions of actin have been contested for more than 20 years but a role for actin as a transcriptional modulator is now firmly established.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence has indicated that nuclear actin, together with nuclear myosin-1 has a general role in transcription (15) and that nuclear actin polymerization is necessary for the expression of factors in nuclear reprogramming, possibly through a chromatin-based mechanism (16,17). Consistent with a general role in nuclear reprogramming, homozygous b-actin knockout in mice is embryonic lethal, and this phenotype seems to be associated with impaired erythropoiesis (18). There is also evidence that actin is involved in the long-range repositioning of gene loci (12,19).…”
mentioning
confidence: 99%
“…However, it was demonstrated previously, that β- and γ-actin isoforms are able to fulfill different functions, e.g. in cell motility [13,22,23,31,74,75], cell division [24], gene transcription [76], endothelial cell motility and neovessel maintenance [77] as well as in developmental processes [78,79]. …”
Section: Discussionmentioning
confidence: 99%